Association between genetically predicted leukocyte telomere length and non-scarring alopecia: A two-sample Mendelian randomization study - Li, Yicheng; Yang, Shuting; Liao, Minjun; Zheng, Zijun; Li, Mengyao; Wei, Xuerong; Liu, Mengqian; Yang, Lei (Frontiers in Immunology, 2023)
Background The most commonly acknowledged non-scarring alopecia are androgenetic alopecia (AGA) and alopecia areata (AA). Previous studies have revealed various risk factors associated with alopecia. However, the relationship between leukocyte telomere length (LTL) and non-scarring alopecia remains unclear. Methods A two-sample Mendelian randomization (MR) analysis was performed to evaluate the causality between genetically predicted LTL and the risk of non-scarring alopecia. MR analyses were performed using the inverse variance-weighted (IVW) method and complemented with other MR methods. Results The summary statistics of the genome-wide association studies (GWAS) for AGA and AA were obtained from the FinnGen biobank, which included 119,185 and 211,428 individuals, respectively. A total of 126 single nucleotide polymorphisms (SNPs) with genome-wide significance were selected as the instrumental variables for LTL. The MR analyses suggested a causal relationship between LTL and AGA, and the risk of AGA increased by 3.19 times as the genetically predicted LTL was shortened by one standard deviation in log transformed form under the IVW method (OR = 4.19, 95% CI = 1.20–14.61, p = 0.024). The other MR methods also demonstrated a similar trend of the effect of LTL on AGA. There was no causal relationship between LTL and AA (p > 0.05). Sensitivity analyses further demonstrated that the current results were less likely to be affected by confounders and bias. Conclusion Our results suggested a potential causal relationship between LTL and AGA, and shortened LTL was associated with an increased risk of AGA.